Laser and Scanning Electron Spectroscopy of Benzyl Hydrogen-4-(Dimethylamino) Benzylidene Hydroxycarbon Hydrazodithiate Schiff’s Base - Hameed, Seenar S.; Ahmed, Dina; Kadhom, Mohammed; Mohammed, Salam (Al-Nahrain Journal of Science, 2024)
The Schiff base compound, benzyl hydrogen-4-(dimethylamino) benzylidene hydroxycarbon hydrazodithiate (BHDBHH), was investigated under continuous wave laser beam irradiation (30 mW), and its chemical properties were analyzed. The material’s chemical properties were found to be affected during laser processing. We examined the chemical properties of the Schiff base using a Scanning Electron Microscope (SEM) and energy-dispersive X-ray (EDX) Spectroscopy. By varying the exposure time, we discovered that longer exposure times resulted in a darker colouration of the compound, even at a low power of 30 mW. This finding led us to conclude that the compound is highly sensitive to laser exposure and can be easily diffused with a more powerful laser. The EDX test revealed a significant reduction in the sulfur element, with more than 50% of it being burned during the exposure.